Identification of key genes and molecular pathways regulating heat stress tolerance in pearl millet to sustain productivity in challenging ecologies - Singh, Swati; Viswanath, Aswini; Chakraborty, Animikha; Narayanan, Neha; Malipatil, Renuka; Jacob, Jinu; Mittal, Shikha; Satyavathi, Tara C.; Thirunavukkarasu, Nepolean (Frontiers in Plant Science, 2024)
Pearl millet is a nutri-cereal that is mostly grown in harsh environments, making it an ideal crop to study heat tolerance mechanisms at the molecular level. Despite having a better-inbuilt tolerance to high temperatures than other crops, heat stress negatively affects the crop, posing a threat to productivity gain. Hence, to understand the heat-responsive genes, the leaf and root samples of two contrasting pearl millet inbreds, EGTB 1034 (heat tolerant) and EGTB 1091 (heat sensitive), were subjected to heat-treated conditions and generated genome-wide transcriptomes. We discovered 13,464 differentially expressed genes (DEGs), of which 6932 were down-regulated and 6532 up-regulated in leaf and root tissues. The pairwise analysis of the tissue-based transcriptome data of the two genotypes demonstrated distinctive genotype and tissue-specific expression of genes. The root exhibited a higher number of DEGs compared to the leaf, emphasizing different adaptive strategies of pearl millet. A large number of genes encoding ROS scavenging enzymes, WRKY, NAC, enzymes involved in nutrient uptake, protein kinases, photosynthetic enzymes, and heat shock proteins (HSPs) and several transcription factors (TFs) involved in cross-talking of temperature stress responsive mechanisms were activated in the stress conditions. Ribosomal proteins emerged as pivotal hub genes, highly interactive with key genes expressed and involved in heat stress response.The synthesis of secondary metabolites and metabolic pathways of pearl millet were significantly enriched under heat stress. Comparative synteny analysis of HSPs and TFs in the foxtail millet genome demonstrated greater collinearity with pearl millet compared to proso millet, rice, sorghum, and maize. In this study, 1906 unannotated DEGs were identified, providing insight into novel participants in the molecular response to heat stress. The identified genes hold promise for expediting varietal development for heat tolerance in pearl millet and similar crops, fostering resilience and enhancing grain yield in heat-prone environments.